Favorable Outcome of Ramsay Hunt Syndrome under Dexamethasone - Josef Finsterer; Arian Bachtiar; Anton Niedermayr (Case Reports in Medicine)
A 20-year-old student under chronic stress developed a painful reddish left ear, vesicles on the left ear, severe left-sided peripheral facial-nerve palsy, and hypoesthesia of the left upper lip, after exposure to a ventilator. Ramsay Hunt syndrome was diagnosed. Instead of prednisolone she received dexamethasone (40 mg/d) but nonetheless recovered completely after 12 weeks.